2021
DOI: 10.1186/s12870-021-02909-7
|View full text |Cite
|
Sign up to set email alerts
|

Natural hybridization between two butterfly bushes in Tibet: dominance of F1 hybrids promotes strong reproductive isolation

Abstract: Background It has been recognized that a certain amount of habitat disturbance is a facilitating factor for the occurrence of natural hybridization, yet to date we are unaware of any studies exploring hybridization and reproductive barriers in those plants preferentially occupying disturbed habitats. Buddleja plants (also called butterfly bush) generally do grow in disturbed habitats, and several species with hybrid origin have been proposed, based solely on morphological evidence. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…For example, a C. × pinnata individual in Jiufeng, Beijing, noted only a few normal achenes per year, while most of them did not develop at all. Except for several prerequisites for natural hybridization, e.g., close kinship, overlapping distribution, similar flowering period, shared pollinators, and same chromosome numbers (Ning et al, 2019), habitat disturbance has been often considered as one of the most important factors promoting hybridization (Arnold, 1997;Li et al, 2017;Liao et al, 2021). In the study area of Beijing and Liaoning Province, we found all the C. × pinnata individuals occurred along the mountain roadside.…”
Section: Causes and Consequences Of Natural Hybridization Between Clematis Speciesmentioning
confidence: 69%
See 2 more Smart Citations
“…For example, a C. × pinnata individual in Jiufeng, Beijing, noted only a few normal achenes per year, while most of them did not develop at all. Except for several prerequisites for natural hybridization, e.g., close kinship, overlapping distribution, similar flowering period, shared pollinators, and same chromosome numbers (Ning et al, 2019), habitat disturbance has been often considered as one of the most important factors promoting hybridization (Arnold, 1997;Li et al, 2017;Liao et al, 2021). In the study area of Beijing and Liaoning Province, we found all the C. × pinnata individuals occurred along the mountain roadside.…”
Section: Causes and Consequences Of Natural Hybridization Between Clematis Speciesmentioning
confidence: 69%
“…Recent studies have shown that F1 hybrids are common in angiosperms and that they can successfully impede gene flow and thus maintain species boundaries between parental species especially in areas where habitat disturbance is high (Liao et al, 2021). Morphologically, C. sect.…”
Section: Causes and Consequences Of Natural Hybridization Between Clematis Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of differences between the means was determined using standard F statistic, and the Bonferroni test was employed for post hoc pairwise comparisons. Where the data did not satisfy the criterion of homogeneity of variance, a Welch statistic was employed, and post hoc comparisons were performed using the Tamhane’s test ( Liao et al., 2021 ). In addition, single flower anthesis, preference of pollinators, fruit and seed sets between S. flava and S. castanea were assessed using a non-parametric Mann-Whitney U-test.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, various patterns of hybridization might occur if RI varied between parental plants and their hybrids. For instance, hybrid zones dominated by F 1 s have been repeatedly detected cross many plant genera and families in recent years ( Milne et al., 2003 ; Zha et al., 2010 ; Liao et al., 2015 ; Zhang et al., 2018 ; Hu et al., 2021a ; Hu et al., 2021b ; Liao et al., 2021 ), indicating that gene flow is fully blocked and RI is nearly complete between parent species. Hybrid zones dominated by F 1 s are usually due to F 1 s having higher habitat-mediated superiority than other genotype classes or a high degree of hybrid sterility ( Milne et al., 2003 ; Yu et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%